Ali razlike v tipu lastništva podjetij odsevajo tudi v menedžmentu njihovih marketinških aktivnosti? - Mumel, Damijan (Akademija MM, 1998)
In the paper we present a part of the results of the international research project which has started in 1995. The main objective of the research was to find out the effects of the process of privatisation and foreign direct investments on marketing of the enterprises in the Central and Eastern Europe. The participants of the research included Hungary, Poland, Bulgaria and Slovenia. As the coordinators of the project were involved the professors from the Aston University in Birmingham (England) as well as from the university of Dublin (Ireland). Into the research project in Slovenia, there were included all of the enterprises with more than 20 employees which were divided into four main categories according to their phase of privatisation process as well as to their ownership in the time of research: a) enterprises in the process of privatisation; b) enterprises which have terminated the process of privatisation; c) organic private enterprises (i.e. enterprises which were established as private entities; d) enterprises with direct foreign investments. The main objective of the paper presented is to show: (a) the differences between particular marketing activities of the enterprises in Slovenia and Hungary, and (b) the differences in some marketing activities of the enterprises according to their ownership and the origin of their capital.
Keywords: corporation; družbena lastnina; Hungary; lastninjenje; Madžarska; management; marketing; podjetje; privatizacija; Slovenia; Slovenija; zasebna lastnina